Cross‐sectional HIV incidence estimation in an evolving epidemic. (21st May 2019) - Morrison, Doug; Laeyendecker, Oliver; Brookmeyer, Ron
Abstract : The cross‐sectional approach to HIV incidence estimation overcomes some of the challenges with longitudinal cohort studies and has been successfully applied in many settings around the world. However, the cross‐sectional approach does rely on an initial training data set to develop and calibrate the statistical methods to be used in cross‐sectional surveys. The problem addressed in this paper is that the initial training data set may, over time, not reflect the current target population of interest because of evolution of the epidemic. For example, the mismatch between the target population and the initial data set could occur because of increasing use of anti‐retroviral therapy among HIV‐infected persons throughout the world. We developed methods to adjust the initial training data set with the goal that the adjusted data sets better reflect the target population. These adjustment procedures could help avoid the time and expense of collecting a completely new training data set from the current target population. We report the results of a simulation study to evaluate the procedures. We applied the methods to a dataset of HIV subtype B infection. The adjustment procedures could be applicable in situations other than cross‐sectional incidence estimation where complex statistical analyses are to be conducted using an initial data set but those results may not be directly transportable to a new target population of interest. The approach we have proposed could offer a practical and cost‐effective way to apply cross‐sectional incidence methods to new target populations as the epidemic evolves.